Peranan Teknologi Dalam Proses Pembelajaran Fisika SMA - I Ketut Mahardika; Muhammad Hasan Muzammil; Devi Fionita Saragih; Frisca Herlina Putri; Nurfadhilah Eka Putri (Jurnal Ilmiah Wahana Pendidikan, 2023)
The purpose of this research is to find out the results of learning physics using science and technology models among students. The method used in this research is a literature review method. The development of increasingly modern technology has become an important means of achieving more effective and efficient educational goals. However, behind that the teacher's role is very large in developing abilities and mastering technology and learning media. In general, high school students are sometimes still not wise in utilizing existing technological developments. Learning media is a method for overcoming all kinds of problems in teaching, not only overcoming problems but can be a factor that influences the development of the learning process for high school students. Achievement of physics learning objectives can be assessed from utilizing understanding in understanding and solving physics problems in everyday life. Students can also adapt to new things that exist, so that the role of technology is very influential in the process and learning outcomes of high school students at school.